2004
DOI: 10.1093/hmg/ddh246
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-permeable AMPA receptors promote misfolding of mutant SOD1 protein and development of amyotrophic lateral sclerosis in a transgenic mouse model

Abstract: Mutant Cu/Zn-superoxide dismutase (SOD1) protein aggregation has been suggested as responsible for amyotrophic lateral sclerosis (ALS), although the operative mediating factors are as yet unestablished. To evaluate the contribution of motoneuronal Ca2+-permeable (GluR2 subunit-lacking) alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA)-type glutamate receptors to SOD1-related motoneuronal death, we generated chat-GluR2 transgenic mice with significantly reduced Ca2+-permeability of these receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
86
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 46 publications
7
86
0
1
Order By: Relevance
“…Furthermore, SOD1 mutants inactivate the highaffinity glutamate transporter GLT1, which is the predominant isoform involved in keeping extracellular glutamate at nontoxic concentrations (26). Crossbreeding of the hSOD1G93A transgenic mice with chat-GluR-B mice, which show reduced Ca 2ϩ -permeability of AMPA channels, delays disease onset and reduces mortality in double-transgenics (27), whereas crossbreeding of the hSOD1G93A transgenic mice with GluR-B(N) mice accelerates disease progression, aggravates severity of motor decline, and decreases survival. Glutamate carboxypeptidase II inhibition protects motoneurons from death in familial ALS, further confirming that glutamate plays a key role in mediating motoneuron death (28).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SOD1 mutants inactivate the highaffinity glutamate transporter GLT1, which is the predominant isoform involved in keeping extracellular glutamate at nontoxic concentrations (26). Crossbreeding of the hSOD1G93A transgenic mice with chat-GluR-B mice, which show reduced Ca 2ϩ -permeability of AMPA channels, delays disease onset and reduces mortality in double-transgenics (27), whereas crossbreeding of the hSOD1G93A transgenic mice with GluR-B(N) mice accelerates disease progression, aggravates severity of motor decline, and decreases survival. Glutamate carboxypeptidase II inhibition protects motoneurons from death in familial ALS, further confirming that glutamate plays a key role in mediating motoneuron death (28).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the best animal models of ALS are provided by rodents harboring mutant forms of the enzyme Cu, Zn superoxide dismutase (SOD1), which are associated with familial ALS in humans. Solidifying the role of Ca-AMPA channels in in vivo models of ALS, recent studies indicate that the rate of progression of MN loss in SOD1 mutant mice varies bidirectionally with the level of expression of these channels (Kuner et al, 2005;Tateno et al, 2004;Van Damme et al, 2005). In addition, Ca-AMPA channels appear to contribute to MN loss in a distinct form of familial ALS, not linked to SOD1 (Lai et al, 2006) and a Ca-AMPA channel blocker was found to be protective in a model of virus induced MN degeneration (Darman et al, 2004).…”
mentioning
confidence: 99%
“…183,184 Then, crossbreeding SOD1 G93A mice with ChAT-GluR2 overexpressing mice, for which AMPA Ca 2+ -permeability is significantly reduced in cholinergic neurons, was shown to delay disease onset (∼19%) and mortality (∼14%) and to alleviate SOD1 protein misfolding. 185 In contrast, crossbreeding of SOD1 G93A mice with GluR2 knockout mice was found to accelerate disease progression and animal death (∼15% for both). 186 As GluR2 mRNA levels are unchanged over the course of the disease in SOD1 G93A mice, 187 but GluR2 protein is specifically decreased in spinal MNs before symptom onset, the beneficial effects of GluR2 overexpression may rely on both a global reduction in Ca 2+ influx through AMPA GluR and on a compensatory GluR2 protein translation defect or instability.…”
Section: Mn Glur Alteration In Als: Zoom In On Glur2 Loss and Editingmentioning
confidence: 99%
“…• Increased survival (SOD1 G93A mice) • AMPA antagonist (+10%) 183,184 • GluR2 overexpression (+14%) 185 • No GluR2 mRNA/protein levels difference in:…”
Section: Pro Conmentioning
confidence: 99%